An overview of microscale indentation fatigue: Composites, thin films, coatings, and ceramics. (September 2021) - Islam, Md. M.; Shakil, S.I.; Shaheen, N.M.; Bayati, P.; Haghshenas, M.
Abstract: There are many applications from computer hardware and sensors to thin films and coatings in which parts are fabricated in small sizes and low thicknesses. Most of these applications could undergo cyclic loading and unloading conditions during their operation. Therefore, cyclic and fatigue evaluations of these components are an essential topic and should be fully understood. In these cases, due to the dimensional limitations, conventional methods of the fatigue experiments encounter challenges and mostly are not accurate or applicable. Nano- and micro-indentation fatigue tests are considered non- or semi-destructive experiments that have opened a new approach to study the cyclic response of these small-sized specimens and thin films. The objective of the present review paper is to evaluate a convenient, reliable, and non-destructive testing approach in the assessment of fatigue (cyclic) response of materials on a small scale. Along with conventional bulk scale fatigue testing methods (i.e. reverse bending, pull-push, multi-axial bending), the depth-sensing indentation testing technique can be employed to study the cyclic behavior of metallic and non-metallic materials especially when a limited volume of the material is available. In this paper, we tried to cover most of the previous studies performed on indentation fatigue of composites, thin films, coatings, and ceramics along with associated discussions and main findings. We covered the physics behind the indentation and the difference between the indentation and conventional fatigue analyses. Followed by that, microstructural evaluations of some of the studies are provided to give readers more insights into this approach. In most applications, the indentation fatigue technique could be a reliable solution due to its accuracy, simplicity, and nondestructive approach in finding out the fatigue and cyclic behavior of materials having a small size or volume. It is worth noting that the loading mode in the indentation fatigue is completely different than the traditional (bulk-scale) fatigue as the tensile segment of the load cycle is not produced in the indentation fatigue (it is a compression-compression loading cycle). Therefore, the controlling mechanisms of failure between small-scale fatigue and bulk-scale fatigue may not be the same.